Pengaruh Model Pembelajaran Kooperatif Tipe Team Assisted Individualization (TAI) Terhadap Kemampuan Berpikir Kritis Siswa di Kelas VIII SMP - Tamsar, Theresia Appri Robelina (CARTESIUS : Jurnal Pendidikan Matematika, 2018)
This study aims to (1) find out whether there is an effect of Team Assisted Individualization (TAI) Cooperative learning model on students' critical thinking skills; (2) to find out whether the critical thinking skills of students who obtain the Cooperative Learning Team Type Assisted Individualization (TAI) model are higher compared to students who obtain the expository learning model. The population in this study were eighth grade students of SMP Negeri 28 Medan. By random sampling selected class III-C as an experimental class as many as 40 students and class III-B as a control class as many as 40 students. The data used in this study is quantitative data. Based on the analysis of research data, the following results were obtained: (1) The regression analysis results obtained equation Y 63 = 63,351 + 11,676X, from the regression results it was found that the Cooperative Assisted Individualization (TAI) learning model had a positive effect on students' critical thinking skills of 11,676 . Where the correlation coefficient is 0.400 and the coefficient of determination is 16%. So it can be concluded that the Cooperative Individualization (TAI) Type Learning Learning model influences students' critical thinking skills, (2) The results of t-test analysis with the value of tcount = 3.717 and t table = 1.666 which means tcount> t table, then the hypothesis H0 is rejected. So that it can be concluded that students who obtain the Cooperative Type Team Assisted Individualization (TAI) learning model are higher than students who obtain the expository learning model.